INTEGRATION OF ARTIFICIAL INTELLIGENCE INTO MODERN EDUCATIONAL PRACTICE: ADVANTAGES AND PROSPECTS - Коробань, Оксана (Modern engineering and innovative technologies, 2024)
The paper examines the impact of modern artificial intelligence (AI) technologies on the educational sphere. The basics of AI and key aspects such as machine learning, adaptive learning, and automated assessment are discussed, including their application